Effect of moisture stress on carbon and nitrogen assimilation and their relation with grain yield of different varieties of soybean (Glycine max) - Chandel, A S; Singh, S K; Saxena, S C (The Indian Journal of Agricultural Sciences, 2012)
A pot experiment was conducted in glass-house during 1988-89 and 1989-90 to study the effect of moisture stress in soybean[Glycine max(L) Merr.]. The soil was silty clay-loam. Eight varieties of soybean (’Bragg’, ’Ankur’, ’PK 327’, ’MACS 13’, ’PK472’, ’PK 308’, ’Kalitur’ and ’Lee’) of different growth habits and maturity were grown at 3 moisture regimes (25, 50 and 75%depletion of available moisture). The soybean varieties differed significantly in response to the degree of moisture stress.Moisture stress Â significantly decreased the dry matter of plant (from 7.1 to 5.5 g/plant), 14,/sup>C assimilation (from318000 to 181 000 dpm/trifoliate), N assimilation (from 0. 86 to 0.54%) and seed yield/plant (from 54.6 to 13. 1 g/plant).’PK 308’ showed maximum 14,/sup>C assimilation under most-stressed condilion (350 000 dpm 14,/sup>C/trifoliate).Maximum reduction due to 75% depletion of available moisture was 63.7, 45.7, 36.1 and 98.0% in 14,/sup>C assimilation, Nassimilation, dry weight of plant and seed yield respectively. ’PK 308’ (48 g/plant) and ’MACS 13’ (41 g/plant) were foundsuperior to the other varieties in seed yield under moisture stress, having 64 and 65% reduction in seed yield.